Percepções dos atores sociais perante o processo de imposições sobre o uso da área e desapropriação de moradores: o caso do Parque Nacional da Lagoa do Peixe, RS - Costa, Maiara Moraes (2023)
The current forms of production and consumption caused the need to create protected areas for the natural ecosystem not be impacted by human actions. Protected areas include Protected Areas (UCs), which are areas of extreme importance for the conservation of local biodiversity and can be divided into Protected Areas of Sustainable Use and Protected Areas of Integral Protection. The category of National Park is inserted in the group of Integral Protection, since it is not allowed to perform the direct use of natural resources available in this area, as well as the compensation of the particular areas inserted in these limits is provided. The Lagoa do Peixe National Park was created in 1986, where in its limits dwelled residents of the region, as artisanal fishermen, farmers and ranchers. At the date of creation there was no legislation that established the obligation of public consultation before the creation of UCs, for this reason socio-environmental conflicts were triggered between the inhabiting community of the region and the managing body of the UC. The objective of this work is to understand the problems faced by social actors regarding the creation of the Lagoa do Peixe National Park in the state of Rio Grande do Sul. Semi-structured interviews were used for data collection. Data processing was performed through content analysis. The research allowed to identify the main socio-environmental conflicts, such as the lack of dialogue, possibilities of impediment of activities, modifications of activities, actions of environmental inspection, the release of fishing and the opening of the bar. The local population develops economic, social and cultural activities in the area along with the available natural resources. With this, it was possible to identify the main actions that can promote the reduction of conflicts in the area. Finally, the research allowed the identification of the perception of social actors, addressing the common points for the reduction or resolution of socio-environmental conflicts.